2024
DOI: 10.1038/s41525-024-00404-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid genomic sequencing for genetic disease diagnosis and therapy in intensive care units: a review

Stephen F. Kingsmore,
Russell Nofsinger,
Kasia Ellsworth

Abstract: Single locus (Mendelian) diseases are a leading cause of childhood hospitalization, intensive care unit (ICU) admission, mortality, and healthcare cost. Rapid genome sequencing (RGS), ultra-rapid genome sequencing (URGS), and rapid exome sequencing (RES) are diagnostic tests for genetic diseases for ICU patients. In 44 studies of children in ICUs with diseases of unknown etiology, 37% received a genetic diagnosis, 26% had consequent changes in management, and net healthcare costs were reduced by $14,265 per ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 143 publications
0
1
0
Order By: Relevance
“…RGS, rapid exome sequencing, and rapid NGS panels are increasingly considered the first-line diagnostic tests for genetic diseases in ICU patients ( 4 ). Considering the increasing daily costs of care in NICUs and PICUs and sophisticated investigations during the diagnosis process, it is likely that the current cost savings per patient diagnosed by rapid sequencing are remarkable ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RGS, rapid exome sequencing, and rapid NGS panels are increasingly considered the first-line diagnostic tests for genetic diseases in ICU patients ( 4 ). Considering the increasing daily costs of care in NICUs and PICUs and sophisticated investigations during the diagnosis process, it is likely that the current cost savings per patient diagnosed by rapid sequencing are remarkable ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis not only facilitates clinical management but also alleviates anxiety among healthcare workers and addresses concerns within the family, ultimately reducing morbidity and mortality rates ( 2 , 3 ). Recent advances in next-generation sequencing (NGS) techniques have decreased costs and time, along with increased availability ( 4 ). Over the last decade, more than 40 studies that involved over 3,500 critically ill pediatric patients suspected of having a genetic condition have used NGS for rapid diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Broadening the application of NGS could significantly enhance its lifesaving potential (Owen et al 2023;Kingsmore et al 2024), as illustrated in a study by Owen et al (2023) that revealed that in a cohort of 112 infant deaths, a number of fatalities could have been prevented if rapid, diagnostic genome sequencing had been applied at the onset of symptoms or immediately upon ICU admission.…”
Section: Introductionmentioning
confidence: 99%